Reducing the dropout rate in higher education - Fernandes, Joana (2020)
This paper is grounded in the human capital theory that considers the effects of education in economy in general and in the individuals’ earnings in particular [1]. For a country to develop it`s important to have an educated and qualified population [2]. However, Portugal, in 2016, was in the top three countries of OECD (Organisation for Economic Cooperation and Development) with the lowest percentage (23.9%) of adult population with a higher education degree, almost 40% below the 35.7% of the OECD average [3]. Therefore, it is relevant to understand students’ motivations and expectations in order to prevent dropout and also to increase the success rate. To do so, a study was conducted in a Portuguese higher education institution in collaboration with the 2nd year marketing undergraduate students. The main objective was to plan and develop measures to prevent dropout as an academic exercise and with student`s insights.